Le point de vue du ministère de la Santé et des Services sociaux - Laberge, Denise (Assurances, 1988)
In the following article, Mrs. Laberge, Assistant Deputy Minister, shows a keen sensitivity to the AIDS problem as a social, medical, ethical and legal dilemma. Mrs. Laberge puts forward in splendid fashion the problems involved, the urgency in solving them and the need for prevention. The author also gives us some of the measures included in the Ministry's plan of action, which basically has two main themes: respecting basic human rights and striving for an international solution, all the while adapting it to our own culture.